A demanda de nitrogênio em plantas sob condições de salinidade depende da tolerância da espécie ao estresse salino? - Ribeiro, Aureliano de Albuquerque (2019)
In many species considered sensitive to salinity it has been observed that the additional application of nitrogen is not able to attenuate the effects of salts.On the other hand, some studies with halophytes have shown different results.In this context, the hypothesis tested in this work was that the response of plants to nitrogen application under saline stress conditions depends on the degree of salinity tolerance of the genotype.The research was carried out in a greenhouse at the Agrometeorological Station of the Federal University of Ceará, Fortaleza, CE. The randomized block design was used in sub-subdivided plots, with two crops (maize and cotton) in the plots, in the subplots, the salinity levels (0.5; 2.0; 4.0 and 6.0 dS m-1) and in the subplots, three nitrogen doses (60, 100 and 140%) of the recommended value for each culture. Four replications were used, totaling 96 experimental units consisting of soil columns, measuring 20 cm in diameter and 100 cm in length. The soil used to fill the columns was Ultisol. Growth, total chlorophyll, leaf gas exchange, mineral nutrition and organic solute accumulation, nitrogen use efficiency and soil nutrient losses were evaluated.The growth and leaf gas exchange data of the evaluated crops showed that the positive effect of additional nitrogen fertilization was only observed at lower salinity levels and that the use of supra-optimal doses intensified the effects of salt stress, especially in corn plants, comparatively. more sensitive to salinity than cotton. Chlorophyll partition and relative index showed clear differences in salinity response and N rates in the two cultures studied.The increase in salinity reduced the efficiency of N utilization, mainly in corn crop and associated with the extra nitrogen dose, did not result in increases of nitrogenous compounds in the leaves and increased the loss of nitrate (NO3-) by leaching.The application of additional nitrogen in plants under saline stress did not reduce the chloride (Cl-) content in the leaves.Increasing salt concentration in the irrigation water increased the electrical conductivity of the saturation extract (CEes), especially at the highest soil depth and nitrogen dose, resulting in reduced osmotic potential in soil solution and growth inhibition root.Soil pH decreased with increasing soil depth and irrigation water salinity.increased salinity of irrigation water caused potassium accumulation in the soil mainly at the highest depths and a high dose of N. In addition, the additional application of nitrogen under high salinity conditions led to NO3- accumulation in the deeper soil layers cultivated with corn.Therefore, responses to additional nitrogen fertilization depend on culture tolerance to salinity and the level of salt stress imposed.